PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE TERHADAP HASIL BELAJAR PADA PEMBELAJARAN SENI MUSIK SISWA KELAS V SD NEGERI 101779 PERCUT - Mei Vina Estetika Br Sembiring; Sri Mustika Aulia; Lidia Simanihuruk; Putra Afriadi; Natalia Silalahi (STKIP Subang, 2026)
This research aims to find out the effect of the use of the think pair share type cooperative learning model on the learning results of music art students in class V of SD Negeri 101779 Percut. This research uses a quantitative approach with Quasi Experimental Design in the form of Nonquivalent Control Group Design in the even semester of the 2025/2026 Academic Year. The research sample consisted of 36 students consisting of 18 V-A class students as a control class and 18 V-B class students as an experimental class. The technique used in sampling using total sampling. Data collection techniques using observation sheets, learning results tests, and documentation. Data analysis uses analytical prerequisite test which includes normality test and homogeneity test, as well as hypothesis test. Based on the research results, pretest and posttest data in the experimental class and control class are normally distributed based on the Shapiro-Wilk test with a significance value > 0.05 and has a homogeneous variance based on the Levene test with a significance value 0,351(> 0.05). The average posttest score obtained by the experimental class was 83.33, higher than the average posttest score of the control class of 65.00. The t-test result obtained a Sig. (2-tailed) value of. 0,000 (< 0,05). so Ho was rejected and Ha was accepted. Thus, the use of the think pair share type cooperative learning model has a significant effect on the learning results of music art students in class V of SD Neger 101779 Percut.